Hallmarks of a new era in mitochondrial biochemistry - Pagliarini, David J.; Rutter, Jared (Genes & development, 2013)
Stemming from the pioneering studies of bioenergetics in the 1950s, 1960s, and 1970s, mitochondria have become ingrained in the collective psyche of scientists as the “powerhouses” of the cell. While this remains a worthy moniker, more recent efforts have revealed that these organelles are home to a vast array of metabolic and signaling processes and possess a proteomic landscape that is both highly varied and largely uncharted. As mitochondrial dysfunction is increasingly being implicated in a spectrum of human diseases, it is imperative that we construct a more complete framework of these organelles by systematically defining the functions of their component parts. Powerful new approaches in biochemistry and systems biology are helping to fill in the gaps.